On Style: An Atelier - Joy, Eileen A.; Kłosowska, Anna (punctum books, 2013)
Scholarship in medieval studies of the past 20 or so years has offered some provocative experiments in, and elegant exempla of, style. Scholars such as Anne Clark Bartlett, Kathleen Biddick, Catherine Brown, Brantley Bryant, Michael Camille, Jeffrey Jerome Cohen, Carolyn Dinshaw, James Earl, L.O. Aranye Fradenburg, Roberta Frank, Amy Hollywood, Cary Howie, C. Stephen Jaeger, Eileen Joy, Anna Klosowska, Nicola Masciandaro, Peggy McCracken, Paul Strohm, David Wallace, and Paul Zumthor, among others, have blended the conventions of academic writing with those of fiction, drama, memoir, comedy, polemic, and lyricism, and/or have developed what some would describe as elegant, and arresting (and in some cases, deliciously difficult) prose styles. As these registers merge, they can produce what has been called a queer historiographical encounter (or in queer theorist Elizabeth Freeman's terms, "an erotohistoriography"), a "poetics of intensification," and even a "new aestheticism." The work of these scholars has also opened up debates (some rancorous) that often install what the editors of this volume feel are false binaries between form and content, feeling and thinking, affect and rigor, poetry and history, attachment and critical distance, enjoyment and discipline, style and substance. As Anna Klosowska writes in her contribution to this volume, The question of style, as it applies to medieval studies, is precisely the overcoming of that dichotomy between Nature and Man: a third element. And when the critique proceeds through the denunciation of the inimitability of someone's style, as if it were the third sex, ungenerative, queer, sterile, sodomitic, lesbian, etc., the critic unconsciously puts his finger on exactly what style is; but that critic is mistaken about the style's supposedly non-generative powers. In fact, style, neither fact nor theory but facilitating the transition between the two, is ... the generative principle itself.